2018
DOI: 10.1007/s11255-018-1953-3
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic selective arterial embolization for renal angiomyolipomas: efficacy and evaluation of predictive factors of significant shrinkage

Abstract: Prophylactic SAE is effective in reducing the size of renal AMLs and decreasing urine erythrocytes with preservation of renal function. Significant shrinkage of AMLs after SAE is modulated by the enhanced area and the background of TSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Multiple renal vascular injuries can also contribute to severe bleeding [10]. In our study, 7 patients (20.0%) had repeated embolization, which was comparable to the rates in the reported literature [8,9]. The decrease in hemoglobin concentration is the most commonly used index for evaluating the severity of bleeding [19][20][21][22].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Multiple renal vascular injuries can also contribute to severe bleeding [10]. In our study, 7 patients (20.0%) had repeated embolization, which was comparable to the rates in the reported literature [8,9]. The decrease in hemoglobin concentration is the most commonly used index for evaluating the severity of bleeding [19][20][21][22].…”
Section: Discussionsupporting
confidence: 80%
“…The rate of DOI: 10.1159/000508797 transfusion was reported between 1 and 55%, while the percentage of embolization varied from 0.6 to 1.5% in previous reports [2,3]. Although several studies had identified the risk factors of vascular complications after PCNL [4][5][6][7][8][9], the related studies are still few in number. Therefore, this study was to reveal the characteristic of severe renal arterial segment bleeding and to assess the outcome of SRAE.…”
Section: Introductionmentioning
confidence: 97%
“…The main reason for this finding may be the low angiomyogenic component of AMLs. 47 Lin et al. 47 showed that AMLs did not significantly decrease in size after embolization if the lesions had little blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…The longest heretofore reported follow-up of patients with renal AML was a mean of 7 years (range, 1.3-20.2). [8][9][10][11][12][13][14][15][16] Longitudinal data on long-term size reduction and retreatment rates are scarce. 8,17 We therefore represent 10-year follow-up of a relatively large cohort of patients who had undergone SAE for renal AML.…”
mentioning
confidence: 99%